1988
DOI: 10.3109/00365548809117224
|View full text |Cite
|
Sign up to set email alerts
|

An in Vivo Model for Evaluation of the Postantibiotic Effect

Abstract: A new experimental model to evaluate the postantibiotic effect (PAE) in vivo was developed using subcutaneously implanted tissue cages in rabbits with normal host defence mechanisms. The rabbits received benzylpenicillin i.v. in a dose giving a free penicillin concentration of 10 X MIC in the tissue cage fluid (TCF). A log-phase suspension of group A streptococci was injected into the tissue cages exposing them to penicillin in vivo. After 2 h bacterial samples were withdrawn, treated with penicillinase and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Three to 4 weeks after the implantation, the tissue cages had sealed with a thin layer of connective tissue and filled with clear, yellowish tissue cage fluid (TCF). Earlier studies have shown that the TCF albumin/serum albumin ratio corresponds very well to the skin albumin/plasma albumin ratio of 0.45 found in humans (3,23).…”
Section: Bacteriasupporting
confidence: 52%
See 4 more Smart Citations
“…Three to 4 weeks after the implantation, the tissue cages had sealed with a thin layer of connective tissue and filled with clear, yellowish tissue cage fluid (TCF). Earlier studies have shown that the TCF albumin/serum albumin ratio corresponds very well to the skin albumin/plasma albumin ratio of 0.45 found in humans (3,23).…”
Section: Bacteriasupporting
confidence: 52%
“…However, C max was much higher in serum than in lungs, with a ratio of 2/1 to 3/1. In contrast, the half-lives were considerably longer in lungs than in serum (20%), resulting in comparable T ϾMIC s. However, in the tissue cage, due to a large volumeto-surface area ratio, an even antibiotic concentration at the infection site is achieved during the induction phase (23). The ␤-lactams accumulated slowly in TCF, and the C max in TCF was lower than that in serum, but the half-life was much longer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations